Isolation, identification and characterization of four cellulolytic actinomycetes and their cellulases (Chittagong University Journal of Biological Sciences, 2013)
Four highly cellulolytic actinomycetous isolates namely SG1, SG2, SG3 and SS1 were isolated from soil samples and provisionally identified as Streptomyces almquistii, S. caeruleus , S. hirsutus and S. endus, respectively. All the isolates showed heavy growth and liquefaction at 50?C and pH 6.5 in Winsteads medium having 1.2% of CMC. The isolates were allowed to grow in Winsteads medium having Asparagine as a nitrogen source with different carbon sources for the maximum production of cellulases. The extracellular protein of the culture supernatant ranged from 1.14 ?g /ml (SG1) to 879.39 ?g /ml (SG3). The reducing sugar level of the culture supernatant ranged from 0.76 ?g /ml (SG2) to 558.33 ?g /ml (SG1). The highest CMC-ase activity (1431.81U/ml) was found with the crude enzyme of the strain SG3. The highest FP-ase activity (1087.11 U/ml) and Avicelase activity (1287.87U/ml) were found with the crude enzyme of SS1. To detrermine the optimum nitrogen sources, the isolates were allowed to grow in Winsteads medium having saw dust for SG1 and SG3, dry leaf for SS1 and SG2 as a carbon source with different nitrogen sources for the maximum production of cellulases. The extracellular protein of the culture supernatant ranged from 35.50 ?g /ml (SG1) to 328.62 ?g /ml (SS1) and the reducing sugar level of the culture supernatant ranged from 3.79 ?g /ml (SG1) to 114.39 ?g /ml (SG3). However the highest CMC-ase activity (1353.78 U/ml), and FP-ase activity (215.90 U/ml) were found with the crude enzyme of the strain SG2 and Avicelase activity (356.06U/ml) was found with the crude enzyme of the isolate SS1 DOI: http://dx.doi.org/10.3329/cujbs.v6i1-2.17241 The Chittagong Univ. J. B. Sci.,Vol. 6(1&2):159-173, 2011